The Impact of Family Intactness on Family Functioning, Parental Control, and Parent–Child Relational Qualities in a Chinese Context - Shek, Daniel T. L.; Xie, Qiuzhi; Lin, Li (Frontiers in Pediatrics, 2015)
The current study investigated the differences between intact and non-intact families in family processes, including systematic family functioning, parental behavioral control, parental psychological control, and parent-child relational qualities. The participants were 3,328 Secondary One students, with a mean age of 12.59 years, recruited from 28 secondary schools in Hong Kong. Four validated scales were used to assess family processes. Results showed that adolescents in non-intact families perceived relatively poorer family functioning, lower level of paternal and maternal behavioral control, lower level of paternal psychological control and poorer parent-child relational qualities than did adolescents in intact families. This generally indicated that family processes were poorer in non-intact families, compared with those in intact families. The theoretical and practical implications of the findings were discussed.